2014
DOI: 10.2351/1.4900795
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of spiral scan paths on cap laser forming

Abstract: Numerical and experimental study of sheet metal hydroforming AIP Conf.An integrated approach to the design of tube hydroforming processes: artificial intelligence, numerical analysis and experimental investigation AIP Conf.Laser forming is a new technology in sheet metal forming process, which has different applications for the industries that have previously used large tools for this purpose. Important parameters for achieving the desirable shape in laser forming process are scan speed, laser power, and scan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A comparison of spiral path movement with a circular irradiation path shows that a smoother curvature will be obtained while using a spiral path strategy. Moreover, the radial circular path forms the workpiece according to the buckling mechanism (BM), whereas the spiral irradiation pattern will result in a gradient mechanism (GM) [85,86]. Different materials, including mild steel, AISI 316 stainless-steel sheet [87], Galvanized iron [88], and AISI 304 stainless steel [89], were successfully formed by the researchers.…”
Section: Doubly Curved Partsmentioning
confidence: 99%
“…A comparison of spiral path movement with a circular irradiation path shows that a smoother curvature will be obtained while using a spiral path strategy. Moreover, the radial circular path forms the workpiece according to the buckling mechanism (BM), whereas the spiral irradiation pattern will result in a gradient mechanism (GM) [85,86]. Different materials, including mild steel, AISI 316 stainless-steel sheet [87], Galvanized iron [88], and AISI 304 stainless steel [89], were successfully formed by the researchers.…”
Section: Doubly Curved Partsmentioning
confidence: 99%
“…The results showed that by selection tailored laser scan patterns and suitable setting of the parameters, tridimensional shapes were formed by high-power diode laser. Hoseinpour Gollo et al 28 investigated the influence of spiral scan paths to create cap by laser forming experimentally and numerically. Laser forming of metal foam was investigated by Roohi et al 29 They studied the influences of three geometrical parameters on bending angle and concluded that relative density of the foam and the mean cell size had the most and the least influences on the final bending angle, respectively.…”
Section: Introductionmentioning
confidence: 99%